Impact of a Brief Family Skills Training Programme “Strong Families” in a Low–Middle-Income-Country: Cambodia - Aala El-Khani; Dina Idriss-Wheeler; Santana Chea; Shatha Darwish; Wadih Maalouf (Children, 2025)
Introduction: Children living in low- and middle-income countries (LMICs) are at increased risk of emotional and behavioural challenges, often linked to caregiver stress and harsh parenting practices. Strengthening family functioning through parenting interventions is a critical strategy for improving child mental health in these settings. The Strong Families programme was developed as a light-touch family skills intervention for high-stress, low-resource environments. Methods: A multisite pilot feasibility and acceptability study was conducted in Cambodia with 40 families. Caregivers and children (aged 8–15) participated in a 3-week intervention, with one session per week. Data were collected using the Parenting and Family Adjustment Scales (PAFAS), the Strengths and Difficulties Questionnaire (SDQ), and the Child and Youth Resilience Measure (CYRM-R) at baseline, two weeks, and six weeks post-intervention. Repeated measures ANOVA and Friedman’s ANOVA were used to assess changes over time. Results: Caregivers showed statistically significant improvements across all PAFAS subscales. For example, coercive parenting scores decreased from 8.13 at baseline to 4.00 post-intervention and 2.33 at follow-up (F(2,78) = 59.76, p < 0.001). Positive encouragement improved from 2.60 to 1.00 and 0.33, respectively (F(2,78) = 27.05, p < 0.001). In terms of child outcomes, SDQ total difficulty scores declined from 20.68 to 16.55 over time (F(2,78) = 7.58, p = 0.001). Emotional problems dropped from 5.60 to 2.38 (χ2(2) = 21.17, p < 0.001), and conduct problems from 4.33 to 2.68 (F(2,78) = 11.35, p < 0.001). Prosocial behaviours increased from 5.60 to 9.45 (F(2,78) = 69.93, p < 0.001). Personal resilience scores rose from 32.70 at baseline to 47.48 at follow-up (χ2(2) = 62.42, p < 0.001), while caregiver resilience improved from 23.63 to 33.63 (χ2(2) = 61.83, p < 0.001). Improvements were particularly pronounced among families with the highest baseline challenges. Conclusions: Findings indicate that the Strong Families programme is feasible and effective in improving parenting skills, family adjustment, child mental health, and resilience in a Cambodian LMIC context. These results reinforce the programme’s potential for integration into broader national strategies to improve psychosocial outcomes for families in high-stress, low-resource environments.